Inusuali tracce di predazione in Ursus spelaeus - Bona F.; Cattaneo C. (2003)
The present study led to the identification of a failed attempt at predation dating about 39,000 years ago. This attack left healed signs of trauma on the cranial vault. The object of this study is a young cave bear (Ursus spelaeus) found at the Caverna Generosa (Lo Co 2694), located on Italian side of Monte Generoso (Como). The study entailed CAT scans and the macroscopic study of the bones which showed how the trauma suffered by the young bear was not lethal: in fact the animal died probably 3 to 12 months after this attack. The morphology of the partially healed lesion has led the authors to the following reconstruction: an attack from behind and above, using probably the two right canines (upper and lower). The list of possible predators includes: Panthera leo spelaea, Crocuta crocuta spelaea, Canis lupus and the cave bears themselves. Given the characteristics of Crocuta crocuta spelaea and Canis lupus, the most likely predators are bear and lion.